Improved disease-free survival with adjuvant radiotherapy in early-stage endometrial cancer: 10-year outcome analysis - Arslan, Suheyla Aytac (J Contemp Brachytherapy, 2020)
PURPOSE: The purpose of this study was to evaluate long-term treatment outcomes and prognostic factors affecting survival of patients with early-stage endometrial carcinoma. MATERIAL AND METHODS: Data of 311 patients with FIGO stage I-II endometrial cancer, curatively treated at two different tertiary centers between June 2001 and December 2016 were retrospectively reviewed. The patients had primary surgery, 74 (24%) received no further treatment, 4 (1%) obtained chemotherapy only, 234 (75%) received radiotherapy, and 24 (7%) received both. RESULTS: Median follow-up time was 102 (range, 3-205) months. During this period, 68 (21.9%) patients died. 5-year and 10-year disease-free survival (DFS) were 76% and 74.3%, respectively. In multivariate analysis, lower uterine segment invasion positivity and no adjuvant radiotherapy were determined as independent unfavorable prognostic factors for DFS. The 5-year and 10-year disease-specific survival (DSS) were 86.8% and 82.2%, respectively. For DSS, high-grade, lymphovascular space invasion positivity, stage II, ≥ 65 age, and no adjuvant radiotherapy were found to be independent unfavorable prognostic markers. CONCLUSIONS: The findings of our cohort have confirmed the importance of adjuvant radiotherapy on long-term early-stage endometrial carcinoma outcome.